Outcome-Based Education (OBE) Policy in Islamic Educational Institutions - Yaniz Naura Naviana Haryadi; Baidi (Research Collaboration Community (Rescollacom), 2026)
The implementation of Outcome-Based Education (OBE) in Islamic educational institutions is a strategic effort to improve the quality of graduates relevant to current needs. However, the adoption of this policy still faces various challenges, particularly in terms of institutional readiness, implementation understanding, and evaluation systems that support an outcomes-based approach. This study used a qualitative approach with a library research method that focused on analyzing Outcome-Based Education policies in Islamic educational institutions. The analysis used a content analysis method. The results show that although learning outcomes have been formulated in curriculum documents, the application of OBE principles in learning and evaluation is still not optimal. This is due to the lack of a comprehensively integrated support system, both in terms of human resources and internal policies. This study concludes that the successful implementation of OBE requires a comprehensive and collaborative institutional approach. These findings are expected to form the basis for formulating Islamic education policies that are more adaptive to the demands of outcomes-based learning.